Ventilación mecánica en el síndrome de dificultad respiratoria aguda en paciente de sexo femenino de 60 años con sepsis de origen abdominal. - De Los Ángeles Barreiro, Cinthya Adali (2020)
The current research work is summarized as follows as introduction temenos that mechanical ventilation as a therapeutic method has had a great development started with the epidemic of polio in Denmark at the end of the 1950’s, and with the birth of the Units of Critical Care in the decade of the 60’s. However, its maximum development aimed at the acute respiratory failure syndrome (SIRA) has been in the last decade, within the theory that supports our work is the concept and everything related to with acute respiratory distress syndrome (ARDS), and of course mechanical ventilation in this type of patients, its use and effective ventilatory modes for ventilatory support of the patient, the main objective is to determine the appropriate initial ventilatory mode to assist the patient. patient with ARDS, to be able to get our objective right it is necessary to study a clinical case which is determined in the ca Chapter 2 in the methodology of the diagnosis, where the evolution of the patient is analyzed, to later reach one of our conclusions that the appropriate initial ventilatory mode to assist the patient with ARDS is the assisted IPPV.